2019
DOI: 10.3390/cancers11121823
|View full text |Cite
|
Sign up to set email alerts
|

The Transfer of Sphingomyelinase Contributes to Drug Resistance in Multiple Myeloma

Abstract: Multiple myeloma (MM) is well-known for the development of drug resistance, leading to relapse. Therefore, finding novel treatment strategies remains necessary. By performing a lipidomics assay on MM patient plasma, we aimed to identify new targets. We observed a dysregulation in the sphingolipid metabolism, with the upregulation of several ceramides and downregulation of sphingomyelin. This imbalance suggests an increase in sphingomyelinase, the enzyme responsible for hydrolyzing sphingomyelin into ceramide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 37 publications
(51 reference statements)
0
36
0
Order By: Relevance
“…70 Exosomal acid sphingomyelinase (ASM) is found to confer the resistance to melphalan or bortezomib to sensitive multiple myeloma (MM) cells. 71 It is likely that exosomal ASM mediates the intercellular communication between drug-resistant MM cells and drug-sensitive ones by increasing the release of drug resistance-associated exosomes. Importantly, amitriptyline, which is usually applied to alleviate the pain of MM patients, is found to inhibit ASM expression resulting in the re-sensitivity to melphalan or bortezomib.…”
Section: Exosomal Protein Cargo Mediating Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…70 Exosomal acid sphingomyelinase (ASM) is found to confer the resistance to melphalan or bortezomib to sensitive multiple myeloma (MM) cells. 71 It is likely that exosomal ASM mediates the intercellular communication between drug-resistant MM cells and drug-sensitive ones by increasing the release of drug resistance-associated exosomes. Importantly, amitriptyline, which is usually applied to alleviate the pain of MM patients, is found to inhibit ASM expression resulting in the re-sensitivity to melphalan or bortezomib.…”
Section: Exosomal Protein Cargo Mediating Drug Resistancementioning
confidence: 99%
“…Importantly, amitriptyline, which is usually applied to alleviate the pain of MM patients, is found to inhibit ASM expression resulting in the re-sensitivity to melphalan or bortezomib. 71 Given that the studies about lipid metabolism pathways in exosomeinduced drug resistance are rare, it is interesting to perform lipidomic analysis to identify the differential expression of exosomal lipids in the future. Notably, the diagnostic or prognostic values of identified exosomal lipids should be further verified in a large number of clinical studies.…”
Section: Exosomal Protein Cargo Mediating Drug Resistancementioning
confidence: 99%
“…EVs play a crucial role in the context of MM pathobiology, and specifically in the crosstalk that malignant PCs establish with other cells of the BMM such as endothelial, stromal, MSCs and immune cells [ 137 , 138 , 139 , 140 , 141 , 142 ]. Such interaction is key both in the progression of the disease and in the onset of pharmacological resistance [ 143 , 144 ]. Moreover, growing experimental evidence indicates that EVs released by MM cells alter bone homeostasis and, therefore, contribute to the onset of MMBD [ 145 , 146 , 147 , 148 , 149 ].…”
Section: Extracellular Vesicle-associated Ncrnasmentioning
confidence: 99%
“…Accumulating evidence shows that EVs could participate in this process [87,88]. It was found that BMSC-derived EVs isolated from both normal donors and MM patients could induce drug resistance in human MM cells; in fact, EVs increased MM cell viability by 25% in the presence of bortezomib and by 9% in the absence of the drug [87].…”
Section: Ev-ncrnas Mediate Drug Resistance In MMmentioning
confidence: 99%
“…It was found that BMSC-derived EVs isolated from both normal donors and MM patients could induce drug resistance in human MM cells; in fact, EVs increased MM cell viability by 25% in the presence of bortezomib and by 9% in the absence of the drug [87]. Furthermore, Faict and colleagues highlighted that MM cell treatment with melphalan or bortezomib induced the release of EVs with a higher amount of acid sphingomyelinase, which could have a role in the MM drug resistance mechanism [88].…”
Section: Ev-ncrnas Mediate Drug Resistance In MMmentioning
confidence: 99%